The Ovine Cathelicidin SMAP29 Kills Ovine Respiratory Pathogens In Vitro and in an Ovine Model of Pulmonary Infection - Brogden, K. A. (American Society for Microbiology, 2001)
Cathelicidins are antimicrobial peptides from sheep (SMAP29 and SMAP34), rabbits (CAP11 and CAP18), rodents (CRAMP), and humans (FALL39, LL37, and h/CAP18). In a broth microdilution assay against nine ovine pathogens, SMAP29, SMAP34, mouse CRAMP, CAP18, CAP18(31), CAP18(28), CAP18(22), and CAP18(21a) were the most active, with MICs as low as 0.6 μg/ml. Other cathelicidins were less active. In lambs with pneumonia, 0.5 mg of SMAP29 reduced the concentration of bacteria in both bronchoalveolar lavage fluid and consolidated pulmonary tissues. Hence, the antimicrobial activity of SMAP29 suggests that it has applications in the treatment of respiratory tract infections.